Sodium–glucose cotransporter-2 Inhibitors in Heart Failure: An Updated Systematic Review and Meta-analysis of 13 Randomized Clinical Trials Including 14, 618 Patients With Heart Failure. Issue 4 (October 2021) - Shrestha, Dhan Bahadur; Budhathoki, Pravash; Sedhai, Yub Raj; Karki, Parag; Gurung, Suja; Raut, Sumit; Damonte, Juan Ignacio; Del, Marco Giuseppe; Mojadidi, Mohammad Khalid; Elgendy, Islam Y.; Patel, Toralben; Patel, Nimesh K.
Abstract : Abstract: Sodium–glucose cotransporter-2 (SGLT-2) inhibitors showed benefit in patients with heart failure. In this updated meta-analysis, we evaluate the therapeutic efficacy and safety of SGLT-2 inhibitors in patients with heart failure. Different electronic databases were searched to find relevant articles. RevMan 5.4 was used for pooling data using a random/fixed-effects model, complemented by several sensitivity and subgroup analyses. A total of 13 randomized clinical trials including 14, 618 patients with heart failure were included in analysis among 6797 studies screened. The overall mortality rate was 12.45% in the SGLT-2 group and 14.67% in the placebo group with 18% lower odds of overall mortality [odds ratio (OR), 0.82; confidence interval (CI), 0.75–0.91] in the SGLT-2 group. Odds of cardiovascular mortality was 18% lower (OR, 0.82; CI, 0.74–0.92) in the SGLT-2 group. The odds of hospitalization for heart failure (HHF) was 38% lower during the study period (OR, 0.62; CI, 0.56–0.68) in the SGLT-2 group. In addition, a benefit was seen for composite outcome HHF or mortality and considering subgrouping based on diabetes status, gender, and age groups. Although genital infection was significantly higher in the SGLT-2 group, the occurrence of severe adverse events, hypoglycemia, urinary tract infection, bone fracture, volume depletion, and other renal events did not differ between the 2 groups. Thus, SGLT-2 inhibitors improved cardiovascular outcomes among patients with heart failure with no significant difference in adverse events. Clinical benefit was comparable in diabetic and nondiabetic individuals, males and females, people in younger and older age groups with underlying heart failure, and HF with reduced ejection fraction. Abstract : Supplemental Digital Content is Available in the Text.